Computational Study of the Structure of a Sepiolite/Thioindigo Mayan Pigment. (1st November 2012) - Alvarado, Manuel; Chianelli, Russell C.; Arrowood, Roy M.
Abstract : The interaction of thioindigo and the phyllosilicate clay sepiolite is investigated using density functional theory (DFT) and molecular orbital theory (MO). The best fit to experimental UV/Vis spectra occurs when a single thioindigo molecule attaches via Van der Waals forces to a tetrahedrally coordinated Al 3 + cation with an additional nearby tetrahedrally coordinated Al 3 + also present. The thioindigo molecule distorts from its planar structure, a behavior consistent with a color change. Due to the weak interaction between thioindigo and sepiolite we conclude that the thioindigo molecule must be trapped in a channel, an observation consistent with previous experimental studies. Future computational studies will look at the interaction of indigo with sepiolite.